Le Corbusier / Volume I. Formative years, 1887-1933 - Livesey, Graham, 1960-; Moulis, Antony (Critical concepts in architecture, 2018)
This four-volume collection of writings on the career and legacy of Le Corbusier traces the various periods of his life from his early training to his final projects. The writings, by Le Corbusier and leading scholars, also explore important themes and specific buildings. The final volume includes articles, some critical of his ideas, which examine his legacy and impact.